2020
DOI: 10.3390/geosciences10090329
|View full text |Cite
|
Sign up to set email alerts
|

Thematic Maps for the Variation of Bearing Capacity of Soil Using SPTs and MATLAB

Abstract: The current study involves placing 135 boreholes drilled to a depth of 10 m below the existing ground level. Three standard penetration tests (SPT) are performed at depths of 1.5, 6, and 9.5 m for each borehole. To produce thematic maps with coordinates and depths for the bearing capacity variation of the soil, a numerical analysis was conducted using MATLAB software. Despite several-order interpolation polynomials being used to estimate the bearing capacity of soil, the first-order polynomial was the best amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…As such, the lowest p-value recorded by the borehole diameter correction factor indicates that it is more influential than the three other correction factors. Karkush et al (2020) explained that the increasing diameter of the borehole suggestively reduced the confining pressure, thus affecting the SPT-N value. In short, this study highlighted the vital role of C B to calculate the sample's shear strength since different sizes of the borehole may affect the shear stress value of soil.…”
Section: Significance Of Anova Findingsmentioning
confidence: 99%
“…As such, the lowest p-value recorded by the borehole diameter correction factor indicates that it is more influential than the three other correction factors. Karkush et al (2020) explained that the increasing diameter of the borehole suggestively reduced the confining pressure, thus affecting the SPT-N value. In short, this study highlighted the vital role of C B to calculate the sample's shear strength since different sizes of the borehole may affect the shear stress value of soil.…”
Section: Significance Of Anova Findingsmentioning
confidence: 99%
“…It is found that up to a depth of 3 m, sandy soil with moorum was established in all the three borehole samples. Since the DFS in all the cases is too less, it can be considered that the soil through which SPTs [30,31] have been conducted is absolutely nonexpansive in nature and does not swell due to groundwater interaction. To support for a safe foundation, the liquid limit values add some more information.…”
Section: Advances In Civil Engineeringmentioning
confidence: 99%
“…The design of shallow foundations requires satisfying two criteria: the first is the adequacy of a shallow foundation to withstand the applied load without failure, and the second is that the settlement shall be within the permissible limits [1]. The bearing capacity and the settlement of the soil beneath the foundation determine how well a foundation performs [2].…”
Section: Introductionmentioning
confidence: 99%